Fluid Retention Caused by Rosiglitazone Is Related to Increases in AQP2 and αENaC Membrane Expression - Jinghua Xu; Mingyue Pan; Xiaoli Wang; Lishi Xu; Lanfang Li; Cheng Xu (PPAR Research)
Peroxisome proliferator activated receptor-γ (PPARγ) is a ligand-activated transcription factor of the nuclear hormone receptor superfamily. The decreased phosphorylation of PPARγ due to rosiglitazone (ROS) is the main reason for the increased insulin sensitivity caused by this antidiabetic drug. However, there is no clear evidence whether the nuclear translocation of p-PPARγ stimulated by ROS is related to fluid retention. It is also unclear whether the translocation of p-PPARγ is associated with the change of aquaporin-2 (AQP2) and epithelial sodium channel α subunit (αENaC) in membranes, cytoplasm, and nucleus. Our experiments indicate that ROS significantly downregulates nuclear p-PPARγ and increases membrane AQP2 and αENaC; however, SR1664 (a nonagonist PPARγ ligand) reduces p-PPARγ and has no effect on AQP2 and αENaC. Therefore, we conclude that in vitro the fluid retention caused by ROS is associated with the increases in membrane αENaC and AQP2 but has little relevance to the phosphorylation of PPARγ.